An Identification of Students’ Responses Based on Solo Taxonomy in Mathematics Learning Toward Learning Activities and Learning Outcomes - Kaharuddin, Andi; Hajeniati, Nining (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Taxonomy solo is a classification of real responses from students. This research aims to identify the effect of students' responses based on a solo taxonomy in mathematics learning on learning activity and learning outcomes. This research is a mixed-method with an explanatory sequential design. The data were collected using observation instruments, questionnaires, interviews, and tests. The data was analyzed inferentially and narratively. Based on the results, students who are at the extended abstract response level are classified as very active and having very high learning outcomes, students who are at the relational response level are identified as active and having high learning outcomes, students who are at the multi-structural response level are identified as active and having moderate learning outcomes, students who are at the Uni-structural response level are identified as active and having moderate learning outcomes, and students who are at the pre-structural response level are identified as less active and having low learning outcomes. Thus, it can be interpreted that students' responses based on solo taxonomy in mathematics learning affect activeness and learning outcomes.